SRUTI AND SMRTI: THE UN-VEDIC DEMARCATION - Purushottama Bilimoria (Journal of Dharma, 1978)
With the growing popularity of the Vedanta system, few will deny that thereis need for an even greater indepth study of Vedanta, particularly Vediinta as associated with the versions of the three grea,t giants of Vedanta: Sankaracarya, Ramanujacarya and Madhavacarya, based on their respective interpretation of Badarayana’s Brabma-siitra, and ultimately of the Upanisads but why stop there? Now, the Vediintins, mentioned above, could be said to have agreed that the world’ is the "manifestation" of Brahman that knowledge of Brahman (or Brabmapiana) is the marga path)which leads to liberation (moksa) of the otherwise bounded’ ’soul’ (jiwa), and further, that Brahman can be known only through the sacrosanct teachings of the scriptures.